The inter-genre nature of the memoirs - Galymzhanova, З.Т.; Baitanasova, Қ.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines the features of memoirs, one of the genres of the novel, which is a kind of epic in literature. The article describes the originality and similarities of memoirs and essays, biographies, travelogues, and other similar works of documentary fiction. Guided by the opinion of research scientists, the main features of memoir novels are individualized, although reliable information makes it look like journalism, through some features of memoirs, an attempt has been made to reveal its belonging to fiction. Memoirs widely use elements of documentary genres of fiction and literature: biographical stories, historical novel, chronicle, novel-autobiography, essay, diary, travel notes, letters, essays (novel-essay, novella-essay), etc. (They are used in memoirs as a historical fact, and in fiction as an artistic method). Memoirs, memoirs and essays, memoirs not only continue the long-standing traditions of the narrative genre in our literature, but also, responding to the spiritual needs of the reader, expand the creative horizons of wordsmiths and improve their literary skills. It is proven that the genre of memoirs is a synthetic structure that combines elements of essays, essays, diaries, epistolary works, autobiographical stories, novellas, novels, chronicles, journalistic articles, notes, and reports.